2017
DOI: 10.1055/s-0037-1604179
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Reproductive Issues Associated with Different Sickle Cell Disease Genotypes

Abstract: To describe the reproductive variables associated with different sickle cell disease (SCD) genotypes and the influence of contraceptive methods on acute painful episodes among the women with the homozygous hemoglobin S (HbSS) genotype. A cross-sectional study was conducted between September of 2015 and April of 2016 on 158 women afflicted with SCD admitted to a hematology center in the Northeast of Brazil. The reproduction-associated variables of different SCD genotypes were assessed using the analysis of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…These are consequences of various factors like poor nutrition, repetitive infections, blood transfusions, painful crisis, and frequent hospital admissions 5. The onset of menarche is delayed in women with SCD4,6 and is strongly associated with the HbSS phenotype compared to the HbSC phenotype 7. Women with SCD have unique risk factors that may affect their ability to conceive, including chronic inflammation, oxidative stress, transfusion-related hemochromatosis, and ovarian sickling, causing ischemia and reperfusion injury to the ovaries.…”
Section: Methodsmentioning
confidence: 99%
“…These are consequences of various factors like poor nutrition, repetitive infections, blood transfusions, painful crisis, and frequent hospital admissions 5. The onset of menarche is delayed in women with SCD4,6 and is strongly associated with the HbSS phenotype compared to the HbSC phenotype 7. Women with SCD have unique risk factors that may affect their ability to conceive, including chronic inflammation, oxidative stress, transfusion-related hemochromatosis, and ovarian sickling, causing ischemia and reperfusion injury to the ovaries.…”
Section: Methodsmentioning
confidence: 99%
“…[ 32 33 ] All our patients had a phenotype of HbSS and some reports have suggested that a delay in menarche is more common with the HbSS phenotype than the HbSC phenotype. [ 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…INTRODUCTION Adolescent and young adults (AYA) with sickle cell disease (SCD) have shown an increase in average life expectancy with continued advancements in therapy and management. 1 A vast majority of patients with SCD live to adulthood, and many AYA with SCD have expectations for their sexual and reproductive health (SRH) that are similar to their healthy peers. 2,3 Unfortunately, AYA women in the United States ages 15-24 years of age experience the highest rates of sexually transmitted infections and unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%